2021
DOI: 10.1017/dmp.2021.49
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of COVID-19 on Physician Moms

Abstract: Objective: This study evaluates the personal and professional experiences of physician mothers during the COVID-19 pandemic and the impact of the pandemic on the lives of physician mothers. Methods: Using social media to reach a broad range of physicians, a convenience sample of physician mothers completed on-line survey posted between April 27-May 11. Members were encouraged to repost on social media and share with personal contacts resulting in a passive snowball sampling effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…Finally, related to the point above, our review revealed that almost no studies we found in our review looked at gender or childcare responsibilities as a factor in the impact of the pandemic on the mental health of oncology HCPs. This is a remarkable oversight as it has been robustly documented that the pandemic has had a disproportionate impact on working mothers, including in medicine [ 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. For example, one study that looked at the impact of the pandemic on male and female oncologists found that in a sample of 541 oncologists, females were much more likely to report that the pandemic affected their professional career in a negative way (85%) when compared to males being asked the same question (76%).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, related to the point above, our review revealed that almost no studies we found in our review looked at gender or childcare responsibilities as a factor in the impact of the pandemic on the mental health of oncology HCPs. This is a remarkable oversight as it has been robustly documented that the pandemic has had a disproportionate impact on working mothers, including in medicine [ 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. For example, one study that looked at the impact of the pandemic on male and female oncologists found that in a sample of 541 oncologists, females were much more likely to report that the pandemic affected their professional career in a negative way (85%) when compared to males being asked the same question (76%).…”
Section: Discussionmentioning
confidence: 99%
“…While a commitment to professionalism was widely expressed by respondents, commentary on gender inequity did surface, reflecting published evidence of the disproportionate adverse effect of the pandemic on women faculty. 34 , 35 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, parents have faced extra challenges with often inadequate workplace and domestic support ( 4 , 8 ). Women and parent physicians disproportionately have shouldered increased burdens and anxiety associated with domestic duties, restrictions in childcare access, homeschooling, and higher productivity expectations given a perceived increase in available time during lockdown ( 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ). The lack of in-person networking and conferences and a decrease in supplemental professional funds have negative impact on career advancement ( 5 , 16 ).…”
mentioning
confidence: 99%
“…The lack of in-person networking and conferences and a decrease in supplemental professional funds have negative impact on career advancement ( 5 , 16 ). Healthcare workers, especially women, have demonstrated an increase in stress and mental health concerns ( 2 , 3 , 15 , 17 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation